1984
DOI: 10.1111/j.1095-8312.1984.tb01676.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of peripheral populations of Nova Scotian Unionidae (Mollusca: Bivalvia)

Abstract: Peripheral populations of eight species of freshwater bivalves (Unionidae) extending their geographic ranges into Nova Scotia, Canada, were examined electrophoretically to determine both the extent of genetic variability within such populations, and whether the hypothesized pathway of colonization across the Isthmus of Chignecto is reflected in patterns of genetic resemblance among these populations. The Nova Scotian species examined could be separated into two groups based on levels of observed heterozygosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 48 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…In the present study, a zone of discontinuity was identified between the Rappahannock and Potomac Rivers that suggests that the populations in the northern and southern portions of the range appear to be heading down different evolutionary paths, which may lead to allopatric speciation. As L. subviridis inhabits headwater streams, it is unlikely that the host would migrate from the upper reaches of one major river to another as restrictions of the host by saline or brackish water will limit dispersal between drainages ( Ortmann 1913; Johnson 1970; Kat & Davis 1984). Given the current levels of the Atlantic Ocean it is unlikely that gene exchange among northern and southern populations of L. subviridis could be re‐established until the next major ice age.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a zone of discontinuity was identified between the Rappahannock and Potomac Rivers that suggests that the populations in the northern and southern portions of the range appear to be heading down different evolutionary paths, which may lead to allopatric speciation. As L. subviridis inhabits headwater streams, it is unlikely that the host would migrate from the upper reaches of one major river to another as restrictions of the host by saline or brackish water will limit dispersal between drainages ( Ortmann 1913; Johnson 1970; Kat & Davis 1984). Given the current levels of the Atlantic Ocean it is unlikely that gene exchange among northern and southern populations of L. subviridis could be re‐established until the next major ice age.…”
Section: Discussionmentioning
confidence: 99%
“…They were compared to the matrix of genetic distances between populations. In the same way hypotheses about the dispersal and evolutionary history of two North American freshwater mussels ( Davis et al ., 1981 ; Kat & Davis, 1984) and a European freshwater fish ( Riffel & Schreiber, 1995) were tested. In all analyses the matrix of shortest (air) distances between any two sampling sites served as the random spatial hypothesis ( Arter, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…It has long been known that the dispersal and population status of unionoid mussels is highly dependent on the availability of appropriate host fishes during the reproductive period (Bauer et al , ; Watters, ; Bogan, ; Vaughn and Taylor, ; Österling et al ., ). For instance, Kat and Davis () as well as Watters () found that extirpation of mussels from several rivers was linked to the disappearance of their hosts. In addition, mussel species have been documented to reinvade streams after reintroduction of their hosts (Smith, ).…”
Section: Introductionmentioning
confidence: 99%